“When Money Matters”: Unpacking the Role of Broad Money in Strengthening Islamic Bank Financing and Economic Growth - Aqwa Naser Daulay; Nawir Yuslem; Nurlaila Nurlaila (Shirkah: Journal of Economics and Business, 2025)
Islamic banking plays an increasingly vital role in promoting inclusive and Sharia-compliant financial services amid economic expansion in Indonesia. This study aims to examine the moderating effect of the ratio of broad money (RBM), as an indicator of financial deepening, on the relationship between Gross Domestic Product (GDP) and Islamic bank financing. Employing a quantitative research design, this study utilizes secondary time-series data and applies moderated regression analysis (MRA) across three models to evaluate the direct and interactive effects of GDP and RBM on Islamic bank financing. The findings reveal that while GDP positively influences Islamic bank financing, the inclusion of RBM as a moderating variable significantly strengthens this relationship, as demonstrated by the significance of the interaction term in the third model. This indicates that financial deepening, reflected in a higher RBM, enhances the capacity of Islamic banks to channel funds into the real economy during periods of economic growth. The study emphasizes the strategic importance of managing broad money supply to support Islamic finance performance and broader macroeconomic goals. Theoretically, the findings contribute to the understanding of how monetary aggregates interact with Islamic financial systems, while practically, they inform policymakers and Islamic financial institutions about the need to align monetary policies with the growth of Islamic banking. Future research should consider additional macroeconomic factors and a broader institutional context to further refine these insights.